Inverse correlation between vascular endothelial growth factor back-filtration and capillary filtration pressures. Issue 9 (9th April 2018) - Kuppe, Christoph; Rohlfs, Wilko; Grepl, Martin; Schulte, Kevin; Veron, Delma; Elger, Marlies; Sanden, Silja Kerstin; Saritas, Turgay; Andrae, Johanna; Betsholtz, Christer; Trautwein, Christian; Hausmann, Ralf; et al.
Abstract: Background: Vascular endothelial growth factor A (VEGF) is an essential growth factor during glomerular development and postnatal homeostasis. VEGF is secreted in high amounts by podocytes into the primary urine, back-filtered across the glomerular capillary wall to act on endothelial cells. So far it has been assumed that VEGF back-filtration is driven at a constant rate exclusively by diffusion. Methods: In the present work, glomerular VEGF back-filtration was investigated in vivo using a novel extended model based on endothelial fenestrations as surrogate marker for local VEGF concentrations. Single nephron glomerular filtration rate (SNGFR) and/or local filtration flux were manipulated by partial renal mass ablation, tubular ablation, and in transgenic mouse models of systemic or podocytic VEGF overexpression or reduction. Results: Our study shows positive correlations between VEGF back-filtration and SNGFR as well as effective filtration rate under physiological conditions along individual glomerular capillaries in rodents and humans. Conclusion: Our results suggest that an additional force drives VEGF back-filtration, potentially regulated by SNGFR.